Renewable Energy Mix Enhancement: The Power of Foreign Investment and Green Policies - Agustina, Ika; Khuan, Hendri; Aditi, Bunga; Sitorus, Sunday Ade; Nugrahanti, Trinandari Prasetya (International Journal of Energy Economics and Policy, 2023)
The objective of this study is to examine and assess the viewpoint of population and economic expansion, as well as foreign investment in the renewable energy sector, by examining the influence of green investment on indexed listed businesses in Indonesia's Sri-Kehati. The dataset utilised in this study include macroeconomic time series data from Indonesia spanning the years 2015 to 2021, as well as issuers indexed under the SRI-KEHATI framework. The data underwent analysis using the multiple regression approach. The study employed an associative research technique and utilised the Eviews 10 programme tool for data analysis. The findings of the study demonstrate a noteworthy positive impact of economic growth on the composition of renewable energy sources. The impact of population growth on the composition of renewable energy sources is shown to be insignificant, but foreign investment is observed to have a notable and adverse influence on the renewable energy mix. The impact of foreign investment on the Renewable Energy Mix is found to be both statistically significant and unfavourable. The variable of economic growth exhibits a noteworthy and favourable impact when moderated by green investment in Sri-Kehati indexed issuers, specifically in relation to the composition of renewable energy sources. The variable of population growth exhibits a noteworthy and favourable impact by means of moderating green investment in the perspective of Sri-Kehati indexed issuer companies regarding the composition of renewable energy sources. The variable of economic growth demonstrates a statistically significant and favourable impact when moderated by green investment in the Sri-Kehati Indexed Issuer Company, specifically in relation to the renewable energy mix. The impact of population growth on the renewable energy mix in the perspective of Sri-Kehati indexed issuer companies is found to be positive and statistically significant when considering the moderation effect of green investment. The variable representing economic growth demonstrates a notable and favourable impact when moderated by green investment in the Sri-Kehati Indexed Issuer Company, particularly in relation to the composition of renewable energy sources. The impact of population growth on the renewable energy mix in the perspective of Sri-Kehati indexed issuer companies is found to be positive and statistically significant when considering the moderation effect of green investment.